DIGITAL DATA MANAGEMENT INFORMATION SYSTEM IN SIDOMUKTI VILLAGE - Safitri, Galuh Melinda; Mawarni, Rima; Rustam, Rustam (Jurnal TAM (Technology Acceptance Model), 2023)
The village is a legal community unit that has regional boundaries that are authorized to regulate and manage the interests of the local community. Based on local origins and customs that are recognized and respected in the NKRI government system. The aim of regional autonomy is based on the development of village communities and ends in community assistance activities with the aim of the government is to provide welfare to the community, but in terms of data collection such as family cards and ID cards which are still manual and not systematic. hampered the process of collecting community data, such as delays in sending data, as well as the unequal distribution of assistance to the poor in the three hamlets. The results to be obtained regarding the management of aid for the poor must be optimized and processed transparently, so that people who wish to receive assistance can be processed quickly and distributed equally as they should. With the existence of a data management information system, web-based assistance is needed to reduce anxiety and errors in dealing with data input.